Acute myocardial infarction due to liquid nicotine in a young man - SARI, İBRAHİM; SÜNBÜL, MURAT; YEŞİLDAĞ, OSMAN (My University, 2014)
[No abstract available]
Keywords: liquid nicotine; myocardial infarction; smoking